The use of Digital Media and Social Media for UKM Temanggung in the era of the Covid-19 Pandemic - Sandi - Supaya; Mardinawati - Mardinawati; Makmun - Riyanto (Admisi dan Bisnis, 2022)
The problem in this research is how to describe the use of digital media and social media in reaching the target market, promoting products, and in implementing marketing strategies.The purpose of this study is to describe the use of digital and social media in the marketing strategy of Temanggung SMEs in the Covid-19 era. Respondents consist of owners and managers of Temanggung SMEs whose products have been included in national, provincial, city or district level exhibitions. Primary primary data were collected through a questionnaire using a survey method. The data were analyzed using the average, the largest, the lowest scoring for each opinion from the respondents. From this study it was concluded that Temanggung SMEs in the era of the covid-19 pandemic very often used digital media and social media to reach the target market, and promote products. SEO, Twitter and Reddit are not used very often. Creation and publishing of content to attract customers' attention, use of media to understand problems, build long-term relationships with target markets, assist and provide advice to customers are not good criteria.